PARADIGMA GABE-AUFGABE DALAM PERUMPAMAAN YESUS TENTANG TALENTA DAN RELEVANSI PASTORAL BAGI UMAT KRISTIANI - Senda, Siprianus S. (STIPAS Keuskupan Agung Kupang, 2023)
Jesus' sermon in Matthew 24-26 is part of what is called a sermon about the end of time. One of the sermons in this section is the sermon on talents in chapter 25:14-30. This sermon has a rich theological meaning as a lesson for the Christian faithful. This paper attempts to explore the richness of the theological passages about this sermon and draw its relevance to the lives of the Christian faithful. The method used is the method of literature with a descriptive analysis approach to find theological messages based on the interpretations of experts. The results of the study show that the Gabe-Aufgabe paradigm is very strong in this parable as a form of life learning for Christians in managing God's grace according to His will for the goodness and salvation of Christians as followers of Christ.